Youth perception and intention towards entrepreneurship on online business / Muharratul Sharifah Shaik Alaudeen and Yong Azrina Ali Akbar - Shaik Alaudeen, Muharratul Sharifah; Ali Akbar, Yong Azrina (2012)
The advancement of internet technologies provide opportunity to people around the world to run business through online by having website, blog and online social network such as Facebook. Even big corporations have websites and Facebook accounts to spur online business. In Malaysia, there are many youth entrepreneurs do online business such as the Internet Millionaire Entrepreneur, Irfan had maximizes usage of internet to gain profit and make it popular to the youth entrepreneurs. In addition, the numbers of online shoppers plus the usage and acceptance towards internet technologies also increased. These indicate the youths spend more time on the internet but do they realize the opportunity to do business over the internet. This research is conducted to determine perception of the youths towards online business entrepreneurship and relationship between perception of the youths and intention to do on line business. This study carried out by distributing questionnaire to 417 youths throughout Peninsular Malaysia. SPSS 18 have been used to analyzed the data. The findings from the research indicate the youths have significant positive on perception towards online business and they have moderate positive intention towards online business. The youths are willing to engage in online business if they have knowledge on online business. The study provides awareness for the university to in cultivate the syllabi on creating website and online business in entrepreneurship syllabi. In addition, the government and relevant agency such as MARA, Ministry of Cooperative and Development can provide substantial training and modules on technical knowledge to run business online and to maintain the web site. Other than that, the youths can realize their potential to maximize the usage of the internet